A Companion to Medieval Translation - Beer, Jeanette M. A. (Arc Humanities Press companions., 2019)
Translation played an essential role throughout the Middle Ages, bridging the gap between literate and lay, and enabling intercourse between languages in multi-lingual Europe. Because of its universality and its vitality, and because it unlocked the door to antiquity's cultural heritage, medieval translation was extremely diverse, ranging from the literality and Latinity of legal documents to the free adaptation of courtly romance. This guide to medieval translation covers religious and vernacular texts, treating translation's multilingual contexts, its didactic and social agenda, and its rhetorical presuppositions. The contributors also address the theoretical and pragmatic problems faced by modern translators of medieval works as they attempt to mediate between past and present.